Impact of sea level rise on tidal energy budget in a macro-tidal coastal bay with archipelago - Lu, Chengzhi; Zhang, Fan; Jia, Jianjun; Wang, Ya Ping (Frontiers in Marine Science, 2024)
With sea level rise (SLR), tidal nuisance flooding has become a growing threat, especially around estuaries with large tidal amplitudes. This study investigated how sea level change affects tides in Hangzhou Bay, a macro-tidal estuary with high SLR rate. By downscaling climate projections to a regional hydrodynamic model, the amplitude of primary tidal constituent (M2) was predicted to increase by 0.25 m in the upper bay, where the amplitude of major diurnal tide (K1) was also predicted to increase by 15%. In addition, the sensitivity of tidal amplitude to mean sea level was examined by a set of numerical simulations with different SLR. It was found that the increase of tidal amplitude is nonlinear to SLR, and the tidal amplitudes almost cease to increase when SLR is over 1.5 m. Although predictions show less amplitude changes in the lower bay, Zhoushan Archipelago around the bay mouth strongly modulates the incoming tidal energy, thus affecting the tidal amplitude in the upper bay. Energy budget analysis revealed that the complex topography, such as narrow channels, in the archipelago area leads to strong horizontal shear, which dissipates approximately 25% of total tidal energy in the bay. On the other hand, around 60% of the energy is dissipated in the bottom boundary layer. However, the bottom dissipation decreases by 4% due to reduced friction, while horizontal dissipation increases by 10% due to enhanced horizontal shear with SLR. This suggests that the strong horizontal shear in the Zhoushan archipelago region can play a more important role in the tidal energy budget in the future.